Differences between sperm sharing and egg sharing are morally relevant - Hodson, Nathan (Journal of medical ethics, 2023)
Sperm sharing arrangements involve a man (‘the sharer’) allowing his sperm to be used by people seeking donor sperm (‘the recipients’) in exchange for reduced price in vitro fertilisation. Clinics in the UK have offered egg sharing since the 1990s and the arrangement has been subjected to regulatory oversight and significant ethical analysis. By contrast, until now no published ethical or empirical research has analysed sperm sharing. Moreover the Human Fertilisation and Embryology Authority (HFEA) does not record the number of sperm sharing arrangements taking place. This paper describes the sperm sharing process providing an analysis of all the UK clinics advertising sperm sharing services. The ethical rationale for egg sharing is described: reducing the number of women exposed to the risks of stimulation and retrieval. This advantage is absent in sperm sharing where donation has no physical drawbacks. The key adverse social and emotional outcome of gamete sharing arises when the sharer’s own treatment is unsuccessful and the recipient’s is successful. This outcome is more likely in sperm sharing than in egg sharing given sperm from sharers can be used by up to 10 families whereas shared eggs only go to one other family. Given its morally relevant differences from egg sharing, sperm sharing requires its own ethical analysis. The HFEA should begin recording sperm sharing arrangements in order to enable meaningful ethical and policy scrutiny.